2018
DOI: 10.18632/oncotarget.25075
|View full text |Cite
|
Sign up to set email alerts
|

Is male infertility associated with increased oxidative stress in seminal plasma? A-meta analysis

Abstract: ObjectivesWe conducted a systematic review and meta-analysis of observational case-control studies to evaluate markers of oxidative stress in seminal plasma of patients with male infertility.BackgroundCurrent evidence links oxidative stress to male infertility, in which multiple markers of oxidative stress have been widely detected, publishing inconsistent results with regard to the role of oxidative stress markers in the evaluation of male infertility. Therefore, a systematic review and meta-analysis on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 84 publications
(116 reference statements)
3
42
0
Order By: Relevance
“…Previous studies have demonstrated lower TAC, SOD and CAT levels in infertile men than in fertile men [13,32]. In addition, a meta-analysis by Huang et al [12] reviewed studies on 3,819 male infertility patients and showed lower levels of antioxidant activity, including TAC, SOD, and CAT, in men with infertility. Previous reports have also detected an increase in antioxidant capacity following antioxidant therapy [17,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated lower TAC, SOD and CAT levels in infertile men than in fertile men [13,32]. In addition, a meta-analysis by Huang et al [12] reviewed studies on 3,819 male infertility patients and showed lower levels of antioxidant activity, including TAC, SOD, and CAT, in men with infertility. Previous reports have also detected an increase in antioxidant capacity following antioxidant therapy [17,33].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in men with IMI, poor semen quality is associated with decreased antioxidant capacity [11]. Both increased ROS production and reduced seminal plasma antioxidant capacity have been reported in infertile men [12].…”
Section: Introductionmentioning
confidence: 99%
“…Another similar study, also concluded that antioxidant treatment (N-acetylcysteine in this case) for 3 months could simultaneously decrease seminal MDA levels while significantly improving sperm concentration and motility in the ejaculate [32]. Thus overall, there is a wide-ranging consensus based on thousands of patients that male infertility is associated with significantly elevated levels of MDA in semen which is, in turn, negatively correlated with levels of seminal antioxidant protection and key aspects of semen quality including sperm count, motility and morphology [33,34].…”
Section: Introductionmentioning
confidence: 86%
“…Building on this body of evidence, the levels of vitamin C, vitamin E and the reduced form of glutathione (GSH; an endogenous antioxidant that can function synergistically with vitamin C [167]), have each been found to be diminished in the semen of asthenozoospermic males compared to normozoospermic controls [168,169]. In contrast to this general trend, data from meta-analyses have failed to document significant changes in the levels of alternative seminal plasma antioxidants such as SOD between males with different forms of infertility (including oligoasthenozoospermia) and that of healthy controls [170], suggesting that not all antioxidants are of equivalent importance in terms of maintaining sperm function. One possible explanation is that the attenuation of antioxidant capacity in infertile individuals may be due, at least in part, to redox driven modifications of specific antioxidant enzymes.…”
Section: Antioxidant Systems In the Male Reproductive Tractmentioning
confidence: 99%